Plasma brain‐derived neurotrophic factor and prefrontal white matter integrity in late‐onset depression and normal aging. (27th January 2013) - Dalby, R. B.; Elfving, B.; Poulsen, P. H. P.; Foldager, L.; Frandsen, J.; Videbech, P.; Rosenberg, R.
<x xml:space="preserve">Abstract</x> Objective To explore the relationship between brain‐derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF), cerebral deep white matter lesions (DWMLs), and measures of white matter integrity in patients with late‐onset depression, with respect to vascular risk factors. Method We examined 22 patients with late‐onset depression and 22 matched controls. Quantification of plasma BDNF and VEGF levels were performed with enzyme‐linked immunosorbent assay (ELISA) kits. Measures of white matter integrity comprised apparent diffusion coefficient (ADC) and fractional anisotropy (FA), obtained by diffusion tensor imaging (DTI). Effects of DWMLs, FA, ADC, and vascular risk factors on BDNF and VEGF were assessed using multiple linear regression. Results The BDNF and VEGF levels did not differ significantly between groups. With pooled data for patients and controls, the BDNF level was positively associated with both number (t = 2.14, P = 0.039) and volume (t = 2.04, P = 0.048) of prefrontal DWMLs and negatively associated with FA in prefrontal normal‐appearing white matter (t = −2.40, P = 0.02), adjusted for age and gender. Smoking and hypercholesterolemia was positively associated with the BDNF (t = 2.36, P = 0.023) and VEGF levels (t = 2.28, P = 0.028), respectively. Conclusion Our results suggest a role for BDNF in the complex pathophysiologic mechanisms underlying DWMLs in both normal aging and late‐onset depression.